2021
DOI: 10.1002/rra.3774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation at a bar confluence on river hydrodynamics: The case study of the Arno River at Greve junction

Abstract: River bars often form at river confluences due to variation in flow discharges or in sediment transport capacity; once these bars are grown, they constitute favourable habitats for vegetation development. In this work, we analysed the effect of vegetation above confluence bars on the hydrodynamics of a river reach. The case study considered is the Arno River reach at the Greve junction, where confluence bars expanded towards the opposite bank. A two-dimensional hydraulic model was implemented through BASEMENT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As suggested by previous ecohydraulic studies and reviews [33][34][35], riverine vegetation's canopy morphometric trends can be easily described by the well-known leaf area index (LAI). This parameter must be properly considered in predictive and numerical modeling of vegetated rivers in urban areas for taking rigorously into account the real-scale impacts of riverine vegetation evolution on flow resistance in vegetated streams, to be then robustly validated by vegetational and water flow measurements acquired during experimental ecohydraulic field campaigns [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by previous ecohydraulic studies and reviews [33][34][35], riverine vegetation's canopy morphometric trends can be easily described by the well-known leaf area index (LAI). This parameter must be properly considered in predictive and numerical modeling of vegetated rivers in urban areas for taking rigorously into account the real-scale impacts of riverine vegetation evolution on flow resistance in vegetated streams, to be then robustly validated by vegetational and water flow measurements acquired during experimental ecohydraulic field campaigns [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the momentum flux of the Yangtze River was large, its flow moved fast and seemed to rush to the right bank and then abruptly changed its direction to the left bank, which is consistent with the experimental results when the confluence ratio was 0.35 and 0.5. In addition, a field study on investigating the effects of vegetation on Arno river (Italy) confluence hydrodynamics conducted by Artini et al (2021) was also compared with our experimental results. Their field survey also observed that vegetation over river bars drives high-velocity flow towards a narrower part of the channel, similar to the top layer of our experimental channel.…”
Section: Discussionmentioning
confidence: 99%
“…Riparian vegetation is an important component of riparian ecosystems ( Stromberg, 2001 ). Riparian vegetation is the primary producer in a riparian ecosystem and plays important functions in energy flow, information flow and biological flow between aquatic and terrestrial ecosystems ( Artini et al, 2021 ). At the same time, vegetation in the riparian zone can control soil erosion and non-point source pollutants in the riparian zone and has unique environmental functions in the whole river ecosystem ( Story et al, 1953 ).…”
Section: Introductionmentioning
confidence: 99%